AKUNTABILITAS ALOKASI DANA DESA DI DESA KORI KECAMATAN KODI UTARA KABUPATEN SUMBA BARAT DAYA 2018: Array - Yohanis Ndoda; Crisistomus E. Oiladang; Rikhardus Seran Klau (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2021)
The success of the implementation of development at the Village level is basically determined by the extent of commitment and consistency of the government and village communities to work together to build the Village. The success of development carried out in a participatory manner starting from planning, implementation to monitoring and evaluation will further ensure the sustainability of development in the village. On the other hand, problems and distrust of one another will easily arise when all communication and information space for the public is inadequate. The purpose of this study was to determine the accountability of the use of Village Fund Allocation (ADD) in village development in 2018 in Kori Village, Kodi Utara District, Southwest Sumba Regency. The use of Village Fund Allocation requires definite accountability related to the use of the funds itself. Accountability for the use of Village Fund Allocation (ADD) in village development is seen from legal accountability, process accountability and program accountability. So far, the management of Village Funds in Kori Village has been running in accordance with the regulations set by the Central Government and the regional / village government itself. Based on the results of interviews conducted by the author with several informants, it can be said that the legal accountability for the use of Village Fund Allocation has not yet been implemented in accordance with applicable regulations where there are village governments that do not comply with all applicable regulations.